MEDIA SOSIAL DAN PERKEMBANGAN ALIRAN KEAGAMAAN PASCA MUNCULNYA GERAKAN ISIS - Angga Teguh Prasetyo (lp2m-uin malang, 2014)
Oleh: Angga Teguh Prastyo FITK UIN Maliki Malang, Email: anggateguh@gmail.com Abstract The existence of social media brings metamorphosis communication behavior among adherents of religious sects. This is because the information obtained from social media is very broad and can be accessed anywhere. Occurrences ISIS movement in Indonesia is also influenced by social media imaging. Consequently, the spread of ISIS teraca flow quickly expanded in Indonesia because it is supported by the speed and breadth of social media networks continues to increase at any time. Such a situation, pose a serious threat the relation between religion and nationality among religions in Indonesia over the appearance of movement ISIS.